If it's not what You are looking for type in the equation solver your own equation and let us solve it.
5(x+7)=-2x+10
We move all terms to the left:
5(x+7)-(-2x+10)=0
We multiply parentheses
5x-(-2x+10)+35=0
We get rid of parentheses
5x+2x-10+35=0
We add all the numbers together, and all the variables
7x+25=0
We move all terms containing x to the left, all other terms to the right
7x=-25
x=-25/7
x=-3+4/7
| 4/5x-2=-1/5x+3 | | -9(y+3)+5(3y-5)=5(y-6)+14 | | 3+1.75x=13.50 | | 37+7x=100 | | {-41/2}x=36 | | 12=(5/9)(f-32) | | (3.45^x)=8 | | 4x=8+3x | | 9v=49+2v | | -4(-12q+8)=-6(q-18)+12q | | 2x-33=-3(2x+3) | | 1=t+6 | | 7159-2146=x | | 8x+16=400 | | 278+319=x | | x=615+76 | | -5-6n=-(1+2n) | | x3=8/729 | | 180+8x+16=6x-60 | | 188+10=x | | 7(4x+1)=5x-6x | | 24(3.25)+18=3y+30 | | 8w+52=142 | | a/15=122 | | 5y−6=3y+2 | | 14x+6=10x-8 | | 0=x^2-5x-3 | | 2=8n/11 | | -8h=-0.39 | | 217x2=x | | |-3x+8|=3 | | 2t+6+6t-30=0 |